1983
DOI: 10.1002/eji.1830130513
|View full text |Cite
|
Sign up to set email alerts
|

T lymphocyte lines producing or vaccinating against autoimmune encephalomyelitis (EAE). Functional activation induces peanut agglutinin receptors and accumulation in the brain and thymus of line cells

Abstract: We studied lines of rat T cells, specifically reactive against myelin basic protein (BP), that were functional in mediating autoimmune encephalomyelitis or in vaccinating rats against induction of active EAE. Herein we report that these functions depended on activation of the cells by incubation with BP or with a T cell mitogen prior to inoculation into recipient rats. Activation was accompanied by the exposure of membrane-binding sites specific for the lectin peanut agglutinin. Accumulation of activated line … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0

Year Published

1984
1984
2004
2004

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 133 publications
(36 citation statements)
references
References 20 publications
2
34
0
Order By: Relevance
“…The present finding that T blasts remain in the thymus for at least 4 wk with no decline in their numbers is thus highly surprising . Nevertheless, the data are in accord with reports that T cells stimulated with myelin basic protein (3,4) or minor histocompatibility antigens (21) can enter the thymus and remain there for at least 2 mo post-transfer. Since the cells recovered from the thymus in these latter studies expressed effector activity only after reactivation with antigen in vitro, blast cells entering the thymus presumably revert rapidly to resting cells.…”
Section: Migration Of T Blasts To the Thymussupporting
confidence: 90%
See 2 more Smart Citations
“…The present finding that T blasts remain in the thymus for at least 4 wk with no decline in their numbers is thus highly surprising . Nevertheless, the data are in accord with reports that T cells stimulated with myelin basic protein (3,4) or minor histocompatibility antigens (21) can enter the thymus and remain there for at least 2 mo post-transfer. Since the cells recovered from the thymus in these latter studies expressed effector activity only after reactivation with antigen in vitro, blast cells entering the thymus presumably revert rapidly to resting cells.…”
Section: Migration Of T Blasts To the Thymussupporting
confidence: 90%
“…As discussed earlier (see Introduction), passive transfer of self antigens into the thymus might serve to promote self tolerance induction . It is notable that autoreactive T cells can return to the thymus after activation in the periphery (3,4). Such homing could be a device to inhibit the further production of T cells with similar self specificity; the blasts might carry MHC/self antigen complexes (see references 22 and 23) into the thymus and display these complexes to newly formed T cells in tolerogenic form.…”
Section: Migration Of T Blasts To the Thymusmentioning
confidence: 99%
See 1 more Smart Citation
“…Initially, radioisotope-labeled (14,15) and, recently, GFP-transduced (4, 16) encephalitogenic T cells were injected into naive animals to induce adoptively transferred EAE, and the markers were traced in lymphoid and target organs during the disease course. Fluegel et al (4) demonstrated that the transferred cells reduce the expression of activation molecules, such as MHC class II Ags, OX40, and IL2Rs, and re-express them after entry into the CNS.…”
Section: Discussionmentioning
confidence: 99%
“…Line A2 reactive to MT was isolated and maintained as described (3 (6) or against experimental autoimmune thyroiditis (EAT) (7). The lymphoblasts were collected, separated from residual accessory cells and from cellular debris by density gradients in some experiments (see Table I), washed twice in PBS, and injected in 1 ml of PBS into the tail vein of nonirradiated Lewis rats.…”
Section: Methodsmentioning
confidence: 99%